Consultant Position at Bangladesh Partnership for Cleaner Textiles (PaCT) program, international finance corporation - Rahman, Mohammad Zahin (BRAC University, 2017)
This internship report is submitted in partial fulfillment of the requirements for the degree of Masters in Development Management and Practice, 2016.